COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 7 NO. 1 (2022) - Jurnal Konversi Energi dan Manufaktur Editor’s (Jurnal Konversi Energi dan Manufaktur, 2022)
Sari et al., in their paper, discusses the hardness and corrosion resistance of hard facings on the surface of carbon steel. This paper aims to analyze the effect of hard facing and heat treatment on low carbon steels on increasing hardness and corrosion resistance. Tyassmadi et al., in their paper, examines the relationship between the implementation of tune-up standard operating procedure of motorcycle to the performance of mechanics in a workshop in Jakarta to know the contribution of the implementation of tune-up standard operating procedure of motorcycle to the performance of mechanics. Susetyo et al., in their paper, conducted a maintenance analysis on the critical components of the degreaser engine at PT X to determine the level of reliability of the main machine. Dwiyati et al., in their paper, carried out the weight lost the copper-nickel/copper-nickel-silicon layer of electroplating in HCl solution. The weight loss determines the effect of the time variation in electroplating coating copper-nickel/copper-nickel-silicon against the corrosion rate in low carbon steel. Basori and Iswadi, in their paper, discuss heating steel material with a carbon content of 0.074 wt. % up to a temperature of 1000 °C, then carried out variations in the holding times in the furnace for 10, 20, and 30 minutes and then quenched with coolant media to see the phenomena that occur. Syamsuir et al. carried out sandblasting with various pressures (4, 5, and 6 bar) to see the characteristics of the formed layer. Syaka et al., in their paper, mixed bioethanol as fuel to see its effect on engine performance and exhaust emissions in a four-stroke single-cylinder gasoline engine. Widodo, in his paper, analyzed shaft wear on the Hitachi Ex-100 front idler backhoe, which often occurs at the Highways Service Office of Kudus Regency, so that in the future damage to this track system can occur.